Rancang Bangun Alat Pengawasan Kondisi Penderita Vertigo Menggunakan Accelerometer Berbasis Mikrokontroler - Yulastri Yulastri; Era Madona; Efrizon Efrizon (Elektron : Jurnal Ilmiah, 2018)
This research designs and makes low-cost portable devices to monitor risk patients losing their balance such as vertigo patients and cause dizziness, fall or not. This tool can determine the patient condition and send information in SMS notification and telephone calls to the patient's family. This tool uses ATmega 328 (Arduino Uno) and tilt sensor HMC5883L (accelerometer) GY-273 as the patient's body tilt detector and GSM SIM800L module for sending SMS notifications and phone calls for remote information while for short range notifications used LEDs and Buzzers. The position detection of vertigo patients works by reading the slope of the patient's body with a tilt sensor (accelerometer) and if the patient's position is no longer robust or unbalanced, then this condition trigger the GSM SIM800L module activate phone calls. When the patient falls and presses the push button, this condition ask the GSM SIM800L module sending SMS notifications. The results of testing performed on the device in detecting falls as much as 30 times, obtained the value of the sensitivity of dizziness activity by 87% and the value of sensitivity on activity fell by 90%. The system requires an average of 8 seconds after the activity falls to send SMS notifications to users of telephone numbers, and also requires an average of 5 to 6 seconds after dizziness to make phone calls to users of telephone numbers. It is expected that the making of this tool can ease monitoring in vertigo patients while on the move